APPLICATION OF ALTERNATIVE APPROACHES FOR INNOVATIVE TECHNOLOGY OBSOLESCENCE IN BULGARIAN ENGINEERING COMPANIES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The purpose of the present work is to present a study of the developed methods of alternative solutions in the assessment of innovation obsolescence in 15 engineering companies in Bulgaria, using the questionnaire method. First, the technology and organization of innovation obsolescence is assessed for each investigated enterprise separately. Second assessment of resources for innovation development. Third manifestation of innovation obsolescence by phases and fourth - Manifestation of obsolescence in individual innovation stages for each investigated enterprise separately, based on planned obsolescence.